2010
DOI: 10.1016/j.cvsm.2010.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Feline Spinal Cord Diseases

Abstract: The objective of this article is to review the recent literature that reports on the most common diseases affecting the spinal cord of cats, and to draw some general conclusions that will be useful to formulate diagnosis and prognosis for feline spinal patients. The most common types of feline spinal cord diseases documented were inflammatory/infectious diseases, and feline infectious peritonitis was the most common disease, representing approximately 50% of all feline myelitis. Neoplasms were documented in ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
69
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(73 citation statements)
references
References 69 publications
4
69
0
Order By: Relevance
“…24 The prognosis is gathered from around 15 case reports or small case series. 5 Cases managed conservatively tended to have a poor outcome, but this Fig. 6.…”
Section: Prognosis In Cats With Intervertebral Disc Diseasementioning
confidence: 94%
See 1 more Smart Citation
“…24 The prognosis is gathered from around 15 case reports or small case series. 5 Cases managed conservatively tended to have a poor outcome, but this Fig. 6.…”
Section: Prognosis In Cats With Intervertebral Disc Diseasementioning
confidence: 94%
“…Marioni-Henry 5 also summarized findings in 44 cats and found an increased prevalence of IVDH at T12-L1 and L4-L6 disc spaces, which are regions maximally dorsiflexed and ventroflexed, respectively, during the stance phase in this species. 5,25 It is suggested that 6% of cats suffering external trauma have SCI. 5 …”
Section: Etiology Of Spinal Cord Injurymentioning
confidence: 99%
“…110 Canine spinal tumors tend to occur in large breeds, typically at an older age (e.g., 9 to 10 years). [105][106][107][108] Vertebral osteosarcoma in cats is usually reported in older patients (e.g., >8 years). 105,106 Boxers may be predisposed to spinal meningiomas.…”
Section: Incidence and Risk Factorsmentioning
confidence: 99%
“…105,106 Meningiomas and malignant nerve sheath tumors (MNSTs) arise most frequently in the cervical spinal cord, and MNSTs are especially prominent in the cervical intumescence area. 107,108 Pathology The category of extradural tumors includes primary and secondary (metastatic or local invasion) vertebral and soft tissue tumors. 109 More aggressive meningiomas (grade II versus grade I) are likely to occur in the thoracolumbar region and in younger dogs.…”
Section: Incidence and Risk Factorsmentioning
confidence: 99%
“…However, pure meningomyelitis and myelitis are rare (TIPOLD; STEIN, 2010). In a recent review of spinal cord diseases in 205 cats, the causes found were: inflammatory/ infectious diseases in 32% of the animals, followed by neoplasms (27%), trauma (14%), hereditary or congenital diseases (11%), vascular diseases (9%), degenerative (6%) and metabolic diseases (1%) (MARIONI-HENRY, 2010). …”
Section: Introductionmentioning
confidence: 99%